Minor bleeding in patients with atrial fibrillation using a non-vitamin-K antagonist oral anticoagulant. (2nd October 2020) - Mitrovic, Darko; Folkeringa, Richard; Veeger, Nic; van Roon, Eric
Abstract: Aims: We sought to investigate the magnitude of minor bleeding and identify risk factors for minor bleeds during non-vitamin-K antagonist oral anticoagulant (NOAC) therapy. Methods: This was an observational cohort study of patients with atrial fibrillation (AF) referred to a regional NOAC outpatient clinic between February 2013 and October 2017. The study population consisted of 875 consecutive patients with AF who visited the NOAC outpatient unit to initiate treatment with apixaban ( N  = 303), dabigatran ( N  = 267) or rivaroxaban ( N  = 305) for long-term ischemic stroke prophylaxis. Minor bleed was defined as every overt bleeding that does not fulfil the criteria of major or non-major clinically relevant bleeding according to the International Society on Thrombosis and Haemostasis. Results: Overall rate of minor bleeds was 19.2 per 100 patient years of follow-up. Bleeding rates for apixaban, dabigatran and rivaroxaban were 26, 8.3 and 23 per 100 patient-years of follow-up. Next to the type of NOAC, the main risk indicators for minor bleedings during NOAC therapy were a HAS-BLED score of 3 or higher and novel anticoagulant use (no history of vitamin K antagonist use). Limitation: This was a retrospective observational study evaluating NOAC treatment in a non-randomized setting. Conclusion: Our data showed that minor bleeds are common in novel NOAC users, especially when using apixaban and rivaroxaban. In the latter two NOACs, hematoma (bruises) and nose bleeds were more frequently observed and accounted for the difference with dabigatran. Besides type of NOAC, a higher HAS-BLED score and novel anticoagulant drug use were associated with an increased risk of minor bleeding.